The South Sudan Conflict: Continentalan and International Implications (Journal of International Studies, 2015)
The South Sudan conflict which started in December 2013 is now entering its second year with continental and international implications far beyond comprehension in terms of human tragedy in one of the world’s newest nations. Continued fi ghting between the government troops and the rebel forces has displaced more than 1 000 000 and killed over 10 0000 people while a humanitarian crisis threatens many more South Sudanese and their neighbouring states. The war risks tearing the country apart as well as creating a potential humanitarian crisis of epic proportions on neighbouring states. Hence, this article examines the continental and international implications of the current South Sudanese confl ict which has roped in the African Union spearheaded by the Inter-Governmental Organization and the United Nations Mission in South Sudan. It argues that the heart of this post-independence conflict in South Sudan is the personal rivalry between President Salva Kiir and his former Vice President Riek Machar. This study attempts to provide a detailed outline of the South Sudanese civil confl ict by conducting an in-depth investigation of secondary data as well as interviews with military peacekeepers imbued with experience on the ground in South Sudan. To address the conflict, this paper suggests that the international community and the country’s leadership need to focus on resolving this personality-driven rivalry to pave way for sustainable peace in the country